AB0318 Abatacept (abt) equivalent to anti-tumor necrosis factor a (tnfa) in terms of joint destruction inhibition: multicenter study of 107 patients treated for 52 weeks. (23rd January 2014) - Ayabe, K.; Takeuchi, K.; Matsushita, M.; Tamura, Y.; Sakurai, T.; Inoue, H.
Abstract : Background: Although two years have passed since the launch of abatacept (ABT) in Japan, little data are available on its efficacy in reducing structural joint damage. We performed a clinical assessment of disease activityand and a radiographic assessment of structural joint damage in 107 patients who had received ABT for 52 weeks. Objectives: Evaluation of results of 52-week multicenter clinical study of ABT for RA Methods: One hundred and seven RA patients who received ABT at a facility participating in a study conducted by the Academy of Clinical Rheumatoid Arthritis Gunma Institute (ACAGI) for at least 52 weeks were included in the efficacy analysis. Efficacy was assessed based on the SDAI scores stratified by MTX treatment and prior treatment with biologics using the LOCF method. Structural analysis was performed at Week 52 in 49 patients who underwent joint radiography and the annual progression rate was assessed using the modified Total Sharp Score (mTSS). Results: Mean SDAI scores decreased from 20.18 at Week 0 to 6.12 at Week 52 in biologics-naive patients (n = 37). Fourteen (37.8%) and 15 patients (40.05%) had remission and low disease activity, respectively. The mean SDAI scores decreased from 24.2 at Week 0 to 11.15 at Week 52 in patients who switched treatments (n = 70). Twelve (17.1%) and 30 patients (42.8%) had remission and low disease activity, respectively. The mean SDAI scores decreased from 21.44 at Week 0 to 9.13 at Week 52 in patients who received a combination of ABT and MTX (n = 63). Seventeen (27.0%) and 25 patients (39.7%) had remission and low disease activity, respectively. The mean SDAI scores decreased from 24.78 at Week 0 to 9.82 at Week 52 in patients who received ABT only (n = 44). Nine (20.5%) and 20 patients (45.4%) had remission and low disease activity, respectively. The retention rate at Week 52 was 68.8%. The annual progression rate at Week 52 was 0.1, showing a significant suppression of joint destruction compared to the estimated annual progression rate at baseline of 8.4. Structural remission (mTSS/year ≤0.5) was achieved in 83.7%. Conclusions: Based on the clinical evaluation and structural analysis at Week 52, more significant effects and better retention can be expected in ABT-treated patients. ABT could be an effective option in RA treatment. Disclosure of Interest: None Declared